Question Making Techniques for Madrasah Ishlahiyah Binjai - Aziza, Jihan Fira; Ramawati, Pitri; Nasution, Nabila Azura; Nur, Mudia Hawa; Liza, Sutia Nur Aulia (Lembaga Riset Mutiara Akbar NOMOR AHU-0003295.AH.01.07 TAHUN 2021, 2024)
Through lecture and practical methods, this training on making hot questions can actually open up teachers' knowledge and understanding of how to compose questions and improve teachers' abilities and skills in making questions at the level of high-level thinking skills so that they can be used to measure the development of students' thinking and reasoning skills. It should be in accordance with the expected final learning outcomes, namely that students can think critically and creatively so that they can apply the knowledge and skills they have to recognize and solve problems faced in everyday life. Training on preparing questions based on Higher Order Thinking Skills (HOTS) aims to increase teacher competence in creating questions that are able to measure students' critical, creative and analytical thinking abilities. Through lecture and practical methods, this training succeeded in increasing teachers' insight and skills in preparing questions that are relevant to the learning needs of the 21st century. This activity involved 35 teachers supported by the PAI Insan Binjai study program. The evaluation shows an increase in understanding and implementation of HOTS-based questions, although several obstacles are still found in practice. It is hoped that the success of this training can become a model for developing teacher competency in the future to create quality students.